Strategy To Increase Technological Sophistication To Increase Helmet Productivity With Technometric Methods And 5W1H : Strategi Peningkatan Kecanggihan Teknologi Untuk Meningkatkan Produktivitas Helm Dengan Menggunakan Metode Teknometrik dan 5W1H - Aziz , Rafly Zulkarnain; Wahyuni, Hana Catur (Indonesian Journal of Innovation Studies, 2023)
Strategy by utilizing technological advances is one way in the process of continuous improvement. UMKM Helmet for Children’s Sidoarjo is an industry engaged in the production of helmets are one of the main equipment that is safe for motorcycle riders. The helmet product produced by the Sidoarjo Children’s Helmet UMKM has been markeed to several cities. The success of the actor’s or personal performance is strongly influenced by aspects of technological sophistication to support businesses in obtaining a accurate data. One strategy that can be used to win the market is to take advantage of technological advances to make continuous improvements. In the production process that has increased, oftentimes market demand has decreased by 40% which usually can deliver 100 addresses every day, down to 60 addresses every day. So it is necessary to conduct a technology assessment in the helmet production process to determine the value of each technology component index. The technometric approach will aassess the level of sophistication of each technology component, namely technoware, humanware, infoware, and orgaware then formulate aproposwd strategy using 5w1h analysis. The results of this study produce a value for the level of sophistication of the technological component, namely technoware is worth 0,645, humanware is worth 0,796, infoware is worth 0,696, orgaware is worth 0,851 and a TCC value is 0,715. From the results of the collection and processing, results are obtained that will become suggestions for improvement and can become the concern and evaluation of UMKM in increasing productivity. Highlights : Importance of Technological Assessment: Evaluating technological components (technoware, humanware, infoware, orgaware) is crucial for understanding strengths and weaknesses. Utilizing Technometric Approach: Technometric analysis provides a quantifiable measure of technological sophistication, aiding in strategy formulation. Emphasis on Productivity Enhancement: Recommendations from the assessment facilitate targeted improvements, enhancing UMKM productivity and market competitiveness. Keywords - Technological Sophistication, Technological Components, Technometrics, 5W1H.